ANALYSIS CODE SWITCHING AND CODE MIXING IN INDONESIAN-ENGLISH TWEETS ON THE @CARATSTALK ACCOUNT (Argopuro: Jurnal Ilmu Bahasa, 2025)
The phenomena of code-switching and code-mixing are essential components of sociolinguistic studies, particularly in multilingual societies that are active on social media. This research was motivated by the widespread use of code-mixing and code-switching in Indonesian K-pop fan communities, particularly on the @caratstalk fanbase Twitter account. This study is significant because such linguistic practices reflect language dynamics and serve as a means of constructing identity within digital communities. This research employs a descriptive qualitative approach with content analysis techniques on public posts and comments on the @caratstalk account. The data were categorized based on the types of code-switching and code-mixing and analyzed in terms of their social context, function, and communicative intent. The findings reveal that the most common forms of code-switching are inter-sentential and intra-sentential switching, while code-mixing typically involves the insertion of English words or phrases into Indonesian sentences. Key factors influencing these practices include expressive needs, the influence of K-pop cultural globalization, and the desire to construct collective identity within fandom communities. Thus, social media proves to be a dynamic linguistic space where language serves as a tool for expression, solidarity, and identity negotiation.Keywords: code-switching, code-mixing, social media, sociolinguistics, K-pop, Twitter.